Abstracts Writing: A Path for Understanding Academic Text of Mathematics - Misdi, Misdi (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2014)
ABSTRACT This is a qualitative study to explore the studentsâ competence in pursuing of abstract writing among the undergraduate students of Mathematics department.The data were collected through classroom observation and self report. By applying self assignment, small group discussion, and presentation, the studentsâ writing experiences were employed in order to discuss the weaknesses and strengths of the mathematic articles given during class discussion; whereas proof-reading, revising, and supervising were also critically provided. As the results, five classes that were involved in the investigation as the sample shows their abilities in applying their best practices based on the suggested method. The results indicate that the undergraduate students of Mathematics were able to reconstruct their ideas in the form of abstract feature, while the abstract writing method was possibly applied in the course of Mathematics. Keywords:Self assignment, Small group discussion, Practice writing, Proof reading, Revising, Supervising